If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sin(2x) = cos(5x) Remove parenthesis around (2x) ins * 2x = cos(5x) Reorder the terms for easier multiplication: 2ins * x = cos(5x) Multiply ins * x 2insx = cos(5x) Remove parenthesis around (5x) 2insx = cos * 5x Reorder the terms for easier multiplication: 2insx = 5cos * x Multiply cos * x 2insx = 5cosx Solving 2insx = 5cosx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Divide each side by '2nsx'. i = 2.5cn-1o Simplifying i = 2.5cn-1o
| b^2-3=6 | | Y=9x-4xy+2x-xy | | 5r^2=10 | | 4y+20=15y-24 | | 3*ln(x+2)=9 | | 112+13p=86 | | 5x-16=x | | 5y-7=y+3 | | 4x-18=17+5 | | 56-6x=-28+8x | | 2x^2+8x-26=0 | | 5q^3(q^4-6q)= | | 96x+51y=6 | | ((6n^3)/(7x^5*y^2))/((3mn^20/(21x^3*y)) | | n/3=2n/6 | | 2x^2+4y=6 | | -2a+5a-12a= | | 5g-9-g=3G+12 | | 3(2p-1)=4p-11 | | 5/12x-12=48 | | 6x^7+22x^6+20x^5=0 | | 6x-13+9+5x=2x+1 | | 16=2/3y | | x/8-x/9=1 | | -2/9z=-4 | | 3.1=7t-1.8 | | -15p-6(5-4p)=6(p-4)-12 | | -3(x+3)-x-6=-4(x+5)+5 | | 3t^2+8t+5=-2t^2 | | 8e^-2x/3=11 | | 8x^3-8x^2+5x-5= | | 8e^-2x/3=3 |